Strategic Engineering for Cloud Computing and Big Data Analytics - Hosseinian-Far, Amin; Ramachandran, Muthu; Sarwar, Dilshad (Springer International Publishing : Imprint: Springer, 2017)
This book demonstrates the use of a wide range of strategic engineering concepts, theories and applied case studies to improve the safety, security and sustainability of complex and large-scale engineering and computer systems. It first details the concepts of system design, life cycle, impact assessment and security to show how these ideas can be brought to bear on the modeling, analysis and design of information systems with a focused view on cloud-computing systems and big data analytics. This informative book is a valuable resource for graduate students, researchers and industry-based practitioners working in engineering, information and business systems as well as strategy. .